Behavioral Control and Reward Sensitivity in Adolescents’ Risk Taking Behavior: A Longitudinal TRAILS Study - Peeters, Margot; Oldehinkel, Tineke; Vollebergh, Wilma (Frontiers in Psychology, 2017)
Neurodevelopmental theories of risk behavior hypothesize that low behavioral control in combination with high reward sensitivity explains adolescents’ risk behavior. However, empirical studies examining this hypothesis while including actual risk taking behavior in adolescence are lacking. In this study we tested whether the imbalance between behavioral control and reward sensitivity underlies risk taking behavior in adolescence, using a nationally representative longitudinal sample of 715 adolescents, of which 66% revealed an increased risk for mental health problems. To assess behavioral control at age 11 we used both self-report (effortful control) as well as behavioral measures of cognitive control (i.e. working memory and response inhibition). Reward sensitivity was assessed with the Bangor Gambling Task. The main finding of this study was that effortful control at age 11 was the best predictor of risk taking behavior (alcohol and cannabis use) at age 16, particularly among adolescents who were more reward sensitive. Risk-taking behavior in adolescents might be explained by relatively weak behavioral control functioning combined with high sensitivity for reward.